Management Research: Discussion on Leadership Study Area (Global Journal of Management and Business Research, 2021)
The study is to review leadership problems in management research. The discussion addresses the problems from theoretical backgrounds and reveal the possible leadership styles and behaviours seen in business world when such problems are experienced. Possible ways of managing the problems in order to minimize the negative effects on business outcomes was also discussed. This discussion will set pace for further specifics research in any organization settings having identified possible problems and how to formulate research questions.